2012
DOI: 10.4236/jmmce.2012.1111115
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behaviour of Al-SiCp Metal Matrix Composites and Optimization Using Taguchi Method and Grey Relational Analysis

Abstract: Aluminium metal matrix composite is a relatively new material that has proved its position in automobile, aerospace and other engineering design applications due to its wear resistance and substantial hardness. Need for improved tribological performance has led to the design and selection of newer variants of the composite. The present investigation deals with the study of wear behaviour of Al-SiCp metal matrix composite for varying reinforcement content, applied load, sliding speed and time. Aluminium metal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…it can be observed that the sliding velocity and sliding distance have a significant effect on the volumetric wear rate. This is in agreement with the laws of adhesive wear and Archard's equation [30]. It is known that as the tensile strengths of the alloys increase, their volumetric wear rate decreases [31].…”
Section: Effect Of Control Parameters On Volumetric Wear Ratesupporting
confidence: 89%
“…it can be observed that the sliding velocity and sliding distance have a significant effect on the volumetric wear rate. This is in agreement with the laws of adhesive wear and Archard's equation [30]. It is known that as the tensile strengths of the alloys increase, their volumetric wear rate decreases [31].…”
Section: Effect Of Control Parameters On Volumetric Wear Ratesupporting
confidence: 89%
“…Several authors have optimized the squeeze casting process parameters for various Aluminum alloy grades using Taguchi method, Grey relational analysis, and genetic algorithm. It was reported that squeeze pressure, die preheating temperature, and melt temperature were found to be the major contributing factors on the mechanical properties of the castings and evaluated the optimal solutions for each factor [22][23][24][25][26][27][28][29]. Among all the available methods of Design of Experiments (DOE), Full Factorial Design (FFD) is a strong candidate in evaluating significant process parameters that can be employed to develop the casting process by evaluation of combined independent factors [30].…”
Section: Cumentioning
confidence: 99%
“…Investigation of the dry sliding wear behavior of aluminum alloy reinforced with SiC was done by Algur et al 7 and to receive data in a controlled way; the design of experiment (DoE) approach was enrolled using Taguchi’s method. Taking into consideration of process parameters such as pertinent to two-body abrasive wear behavior and multiple quality attributes of the material, the optimization of hybrid aluminum composites was done by Ghosh et al 8 using Taguchi’s gray relational analysis (GRA).…”
Section: Introductionmentioning
confidence: 99%